THE LAW OF LAND SELLING ABOVE THE SALE OF OTHERS ACCORDING TO SHEEK IBNU HAJAR AL-ASQALANI (Case Study of Sialang Gatap Village, Kualuh Hilir) - Hasibuan, Muhammad Syahyuti; Zahara, Fatimah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Researchers conducting this research aim to examine and analyze the law of buying and selling land that is carried out on land that has previously been traded by other people, by focusing on the views according to Sheikh Ibnu Hajar Al-Asqalani. This research was conducted using a case study conducted in Sialang Gatap Village, Kualuh Hilir District, Labuhan Batu Utara Regency, as a concrete form of this phenomenon. The method used in this study is through a living case study approach, which is an approach to a problem related to law whose process is ongoing or has not been completed. This study uses data collection techniques using observation, unstructured interviews, and documentation